Updated prevalence rates of overweight and obesity in 11- to 17-year-old adolescents in Germany. Results from the telephone-based KiGGS Wave 1 after correction for bias in self-reports. (December 2015) - Brettschneidera, Anna-Kristin; Schaffrath Rosario, Angelika; Kuhnert, Ronny; Schmidt, Steffen; Wiegand, Susanna; Ellert, Ute; Kurth, Bärbel-Maria
Abstract Background The nationwide "German Health Interview and Examination Survey for Children and Adolescents" (KiGGS), conducted in 2003–2006, showed an increase in the prevalence rates of overweight and obesity compared to the early 1990s, indicating the need for regularly monitoring. Recently, a follow-up—KiGGS Wave 1 (2009–2012)—was carried out as a telephone-based survey, providing self-reported height and weight. Since self-reports lead to a bias in prevalence rates of weight status, a correction is needed. The aim of the present study is to obtain updated prevalence rates for overweight and obesity for 11- to 17-year olds living in Germany after correction for bias in self-reports. Methods In KiGGS Wave 1, self-reported height and weight were collected from 4948 adolescents during a telephone interview. Participants were also asked about their body perception. From a subsample of KiGGS Wave 1 participants, measurements for height and weight were collected in a physical examination. In order to correct prevalence rates derived from self-reports, weight status categories based on self-reported and measured height and weight were used to estimate a correction formula according to an established procedure under consideration of body perception. The correction procedure was applied and corrected rates were estimated. Results The corrected prevalence of overweight, including obesity, derived from KiGGS Wave 1, showed that the rate has not further increased compared to the KiGGS baseline survey (18.9 % vs. 18.8 % based on the German reference). Conclusion The rates of overweight still remain at a high level. The results of KiGGS Wave 1 emphasise the significance of this health issue and the need for prevention of overweight and obesity in children and adolescents.